Socio-legal aspects of low voter turnout - Jackiewicz, Maksymilian (Management and Administration Journal, 2023)
The purpose of this publication is to explain the basic value of democracy, which is to participate in the general elections. Issues raised are intended to explain the reasons for targeting citizens to participate in elections, as one of the basic tasks of a responsible, aware of their rights of society. A general election is an important aspect in the lives of citizens, which should not be underestimated. In this way they are expressed aspects such as membership, interest in current affairs, opinion, responsibility. All these factors have a huge impact on shaping the direction in which it is to be in Poland in the future. This responsibility rests precisely on society through their conscious choice. Lack of involvement in social life by not participating in the elections could have negative effects impacting on future generations. Play an important role in raising awareness of state institutions that perform functions citizens. In cope with such tasks, these institutions should arrange a variety of actions, designed to encourage citizens to participate actively in the selection of candidates, deciding on the most important issues in the country. It is this attitude and commitment is the basis of conscious striving for democracy.